PELAKSANAAN PERATURAN WALIKOTA NOMOR 31 TAHUN 2009 TENTANG TARIF ANGKUTAN PENUMPANG UMUM DENGAN ANGKUTAN TAKSI DI KOTA PEKANBARU TAHUN 2009-2012 - Hadi Nofrinal; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research entitled " Government Policy Study In Cultivation Prisoner ( Studi Lembaga Pemasyarakatan Kelas II a Pekanbaru). Thing that melatar back to back him is about persolan that mysterious palinf in institution socialization that always been public view, namely custody room capacity excess because the low socialization institution capacity, then stiffness rate recidivism in institution socialization, obstacle facility and infrastructure cultivation, its shortage employee or socialization institution staff, and its shortage operational costs in support implementation cultivation. Disisi is other problem that not should happened by prep inside institution socialization is still free narkoba circulation in institution socialization and happened by him fight inter coequal prisoner.Rumusan internal problem this research is . Why Government Policy In Cultivation Prisoner ( Pemasyarakatan kelas II a Pekanbaru study Institution) not yet optimum. This research aimed to know government policy implementation in cultivation prisoner in II a Pekanbaru class socialization institution and constraints faced in pemerintrah policy implementation in cultivation prisoner in II a Pekanbaru class socialization institution. Benefit from this research is provide donation thinking for law enforcer apparatus especially selakau socialization institution employee like educator and cultivation prisoner.Method used in this research is descriptive method with qualitative and quantitative approach. Technique data collection used is observation, interview, and kuisioner. Data source used is primary data that obtained from field and secondary data that obtained from place research that usually has been provided. Research result data obtained by policy that used by institution socialization refer to regulation in government regulation number 31 year of 1999 article about 7 cultivation prisoner. This result research get constraints happened in prisoner cultivation process namely, obstacle in thing facility and infrastructure, its shortage employee or socialization institution staff, and its shortage operational costs. And based on C.I Harsono theory that purpose cultivation is "Kesadaran", in this case awareness thing prisoner awareness not yet able to own awareness fully like inner awareness know potential self which said defective 11 people from 20 people and in awareness phase attainer that high also beum able owned by prisoner namely 55 % or 11 people which said defective.Keyword:Policy, Cultivation, Prisoner, Institution Socializatio